The Correlation Between Nurses’ Knowledge of Triage and the Accuracy of Triage Level Interpretation in the Emergency Department of the Government Hospitals in the City of Semarang - Chanif, Chanif; Nursalam, Nursalam; Sriyono, Sriyono; Yuniasari, Lukluk; Pranata, Satriya; Armiyati, Yunie (Scripta Medica, 2023)
Background/Aim: Knowledge about triage has been identified as one of the factors influencing patient outcomes in the emergency room. Nurses' knowledge regarding triage is necessary in order to work effectively in managing patients, as swift and accurate actions depend on the nurses' acquired knowledge. The aim of this research is to determine the correlation between nurses' knowledge of triage and the accuracy of triage level interpretation.Methods: The research method was carried out using a questionnaire sheet for the triage knowledge variable and an observation sheet for the variable of accuracy in triage level interpretation. This research was conducted in May-June 2023 at Tugurejo Regional General Hospital, K.R.M.T Wongsonegoro Regional General Hospital, and Dr. Kariadi General Hospital. The independent variable in this study was nurses’ knowledge and the dependent variable was the accuracy of triage level interpretation.Results: Based on the results of the bivariate analysis, nurses' knowledge have a correlation with the accuracy of triage level interpretation with a p-value of (0.000 < 0.05).Conclusion: There is a correlation between nurses’ knowledge of triage and the accuracy of triage level interpretation.